Engineered Metallacycle‐Based Supramolecular Photosensitizers for Effective Photodynamic Therapy. Issue 15 (2nd March 2023) - Tu, Le; Li, Chonglu; Xiong, Xiaoxing; Hyeon Kim, Ji; Li, Qian; Mei, Longcan; Li, Junrong; Liu, Shuang; Seung Kim, Jong; Sun, Yao
Abstract: Although metallacycle‐based supramolecular photosensitizers (PSs) have attracted increasing attention in biomedicine, their clinical translation is still hindered by their inherent dark toxicity. Herein, we report what to our knowledge is the first example of a molecular engineering approach to building blocks of metallacycles for constructing a series of supramolecular PSs (RuA–RuD ), with the aim of simultaneously reducing dark toxicity and enhancing phototoxicity, and consequently obtaining high phototoxicity indexes (PI). Detailed in vitro investigations demonstrate that RuA–RuD display high cancer cellular uptake and remarkable antitumor activity even under hypoxic conditions. Notably, RuD exhibited no dark toxicity and displayed the highest PI value (≈406). Theoretical calculations verified that RuD has the largest steric hindrance and the lowest singlet‐triplet energy gap (Δ E ST, 0.61 eV). Further in vivo studies confirmed that RuD allows safe and effective phototherapy against A549 tumors. Abstract : A series of high‐performance photosensitizers (PSs) was designed and synthesized using a molecular engineering approach for building blocks of Ru II metallacycles. Subsequently, the photosensitizer with the highest reactive oxygen species (ROS) generation efficiency, biocompatibility, and phototoxicity index (PI), RuD, was selected for safe and effective photodynamic therapy in vitro and in vivo.